PENERAPAN PENDEKATAN OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA - Sarah Inayah (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2020)
The aim of this research is to find out the increasing of the critical thinking skills of student’s mathematical by using open ended approach, along with to find out how the student’s attitude concerning of the learning by using open ended approach. This research uses the quasi experiment with non equivalent control group design approach method. The population of this research is all of the students in VIII class at SMP 1 Karangtengah, while the sample used as much as two classes, that are VIII H class as the control class and VIII I class as the experiment class, which are sampling by using sampling purposive technique, that is sampling technique by certain criteria. In the experiment class gave the treatment by using open ended approach, while the control class gave the treatment as usual by the teacher in learning activities. The research shows the increase of the critical thinking skills of student’s mathematical by using open ended approach is better than the critical thinking skills of student’s mathematical by using common learning, and commonly, inquiry scale attitude shows the student’s response concerning open ended learning-approach is positive.